1998
DOI: 10.3109/01485019808987942
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Combined GnRH/HCG Therapy in Boys with Undescended Testicles: Evaluated in Relation to Testicular Localization within the First Week After Birth

Abstract: Among 509 boys referred with undescended testicles, 112 had true undescended testicles unilaterally and 62 bilaterally. Patients with true undescended testicles were offered hormonal treatment unless the condition was associated with hernia or previous operations. Boys less than 5 years old were primarily treated with gonadotrophin releasing hormone (GnRH), while boys more than 5 years old were primarily treated with human chorionic gonadotrophin (hCG). If the effect of the primary treatment was insufficient t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…However, proof of the efficacy of hormonal therapy for undescended testis is limited as yet. There was a report that the practice of hormone therapy for less than 1 week was almost not effective for boys with unilateral undescended testis although it was found to be effective in about 56% of boys with bilateral undescended testis [25]. A number of studies have been conducted regarding hormone therapy among patients with retractile testis, and testicular descent was achieved by short-term hormone therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, proof of the efficacy of hormonal therapy for undescended testis is limited as yet. There was a report that the practice of hormone therapy for less than 1 week was almost not effective for boys with unilateral undescended testis although it was found to be effective in about 56% of boys with bilateral undescended testis [25]. A number of studies have been conducted regarding hormone therapy among patients with retractile testis, and testicular descent was achieved by short-term hormone therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The studies generally agree with Pyorala et al [78] that therapeutic success is greater when the testis is in a lower position and age is not a factor. In addition, four trials reported that it is more effective in bilateral cases rather than unilateral ones [81][82][83][84].…”
Section: Efficacymentioning
confidence: 96%
“…hCG and GnRH, alone or combined in various treatment schedules, are the main used hormones [2, 3, 4, 5, 6, 7, 8, 9, 12, 13, 14, 15], but their efficacy remains a debated issue [1, 2, 4]. In fact, great variation in testicular descent has been reported [2, 4], ranging from 0 to 90% [2, 3, 4, 5, 6, 7, 8, 9, 11, 12, 13, 14, 15]. The inclusion of heterogeneous patient populations regarding the type of cryptorchidism (unilateral or bilateral), the site of testicular retention (abdominal or impalpable, inguinal, suprascrotal, high scrotal), and the age at hormonal treatment (from 1st year of life to adolescence) are considered causes of the different clinical results [1, 2, 3, 4, 13].…”
Section: Discussionmentioning
confidence: 99%
“…Hormonal treatment of cryptorchidism has been used to stimulate the secretion of testicular androgens and to override the imbalance leading to testicular retention [3, 11]. hCG and GnRH, alone or combined in various treatment schedules, are the main used hormones [2, 3, 4, 5, 6, 7, 8, 9, 12, 13, 14, 15], but their efficacy remains a debated issue [1, 2, 4]. In fact, great variation in testicular descent has been reported [2, 4], ranging from 0 to 90% [2, 3, 4, 5, 6, 7, 8, 9, 11, 12, 13, 14, 15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation